DESIGN AND CFD ANALYSIS OF 1 KW PICO HYDROPOWER SIMULATOR WITH CENTRIFUGAL WATER PUMP AND FRANCIS TURBINE - Sutisna, Nanang Ali; Aditama, Fauzan Yasa (Media Mesin: Majalah Teknik Mesin, 2025)
Simulation is essential for a design study. This article illustrates the result of a research aimed to design andbuild a Pico Hydro Generator simulation system using a water pump as a source of water flow. Pico HydroGenerator is a small-scale power generation technology that utilizes water energy as a renewable energy resource.Through this simulation system, the design and testing of the Pico Hydropower simulator design can be carriedout to determine the efficiency value of the design. The planning process begins by determining the specificationsof the water turbine to be used, including water discharge, headwater, and the required capacity. Based on thesedata, it is possible to select the type of water pump that is suitable for the needs of the turbine. Then the design ofPico Hydropower components such as turbines, generators, water tanks, water channels, and system panels isdesigned. The design process uses CAD (Computer Aided Design) software to design parts and assemblies on thesimulator. Then the design performance will be analyzed using Computational Fluid Dynamic (CFD) software.The final result of this study is a Pico Hydropower simulator design that has been optimized and can be simulatedby using a water pump as a flow source. This simulation system can allow research and development in the formof learning tools for students to understand how Pico Hydro power plants work and how to calculate theirefficiency.